If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -3 = 9y + -4y Reorder the terms: -3 + 6y = 9y + -4y Combine like terms: 9y + -4y = 5y -3 + 6y = 5y Solving -3 + 6y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -3 + 6y + -5y = 5y + -5y Combine like terms: 6y + -5y = 1y -3 + 1y = 5y + -5y Combine like terms: 5y + -5y = 0 -3 + 1y = 0 Add '3' to each side of the equation. -3 + 3 + 1y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1y = 0 + 3 1y = 0 + 3 Combine like terms: 0 + 3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 5k-(2k-10)=25 | | 14.50-p=53.00 | | 3(2c+5)=39 | | -(3k+4)=6k-3(3k+2) | | 15m+20=8m-22 | | 6x-3y=8x+10 | | 7+8x+2x=7 | | 48x^2-58x+15=0 | | 6x+16=4x-10 | | X^2+X+1-i=0 | | 37+8x=(7-x) | | X=(13/5)*y | | X=(13/5)×y | | 14=.5(8x+12) | | X=(13/5)y | | 14=.5 | | (6y-5x)(3y-7x+4)= | | 3/4g=28 | | 6x+16=3x+17 | | 3h-6+2h=-2+h | | X^2-2ax-1=0 | | 5(2-x)-3(4-2r)=20 | | 2b+3=b+19 | | 15x^3+3x= | | 3l-6+2l=-2+l | | 6i/5+3i= | | [2x-2]=6 | | 5y=7x+2 | | 189=9-9x | | -(0.79k+0.227)=-(2.09k+0.838) | | 6/4+6i= | | p^3(e^5p-7)-(6p/2_p^2) |